Bit error rate minimisation using SLM technique in TFT-OFDM for mobile large-scale MIMO systems. (2018) - Meenakshi, R.; Indumathi, P.
In the case of large-scale Multiple-Input Multiple-Output (MIMO) systems, the Time-Frequency Training (TFT) of OFDM and their transmission schemes can solve the high-dimensional problems of channel estimation in the wireless communication systems. In the wireless technologies, their physical layer can carry out the process of transmission inside the variable channels. The noise that was induced by these channels may also degrade the performance of the system that concerns Bit Error Rate (BER). So, in this paper, a Selection Mapping (SLM) technique in the TFT-OFDM for the mobile large-scale MIMO systems has been proposed for minimising the BER. This SLM technique tends to produce the data with these phase vectors for discovering the candidate vectors and also the IFFT operation which is done on the TFT-OFDM symbol that obtains a minimum BER that has to be transmitted. This scheme performance has been compared with that of the existing TDM-OFDM with BER. The performance analysis of MIMO TFT-OFDM is considered for biomedical signal transmission through high-speed wireless transmission. The results of this experiment prove that the proposed scheme achieves a better performance than that of the existing schemes.